Effects of Strategic Information and Communication Technology (ICT) on Airports’ performance in Kenya - Koros, Rosemary Chebet; Namusonge, Prof. G. S.; Sakwa, Prof. M.M. (IJRDO - Journal of Business Management, 2018)
This study aimed to determine the effect of Strategic Information and Communication Technology (ICT) on Airports’ performance. The study findings indicated correlation coefficient of 0.561 implying a positive relationship between Strategic Information and Communication Technology and airport performance. This was evidenced by the p value of 0.000 which is less than that of critical value (0.05). The study concluded that there was a significant positive relationship between Strategic Information and Communication Technology and airport’s financial performance.